Inactivation of foodborne viruses by novel organic peroxyacid-based disinfectants - Bouchard, Simon; Paniconi, Teresa; Jubinville, Éric; Goulet-Beaulieu, Valérie; Goetz, Coralie; Marchand, Patrick; Jean, Julie (Frontiers in Microbiology, 2023)
Viruses are responsible for most enteric foodborne illnesses worldwide. The foods most frequently involved are fresh fruits and vegetables since they undergo little or no processing. Washing with a chemical disinfectant is a convenient way of inactivating viruses on foods. Peracetic acid, widely used as a disinfectant in the food industry, has the drawback of leaving a strong odor and is ineffective alone against some foodborne viruses. In this study, four disinfectants, namely perlevulinic acid with or without sodium dodecyl sulfate, peracetic acid and a commercial peracetic acid-based disinfectant were tested on murine norovirus 1 (MNV-1), hepatitis A virus (HAV) and hepatitis E virus (HEV). Disinfectant concentrations were 50, 80, 250, 500 and 1000 mg L-1 and contact times were 0.5, 1, 5 and 10 min. Under these conditions, perlevulinic acid supplemented with 1 % SDS reduced MNV-1 infectious titer by 3 log cycles versus 2.24 log cycles by peracetic acid within 0.5 min. On stainless steel at 80 ppm, only peracetic acid produced 3-log reductions within 0.5 min. None of these peroxyacids was able to reduce infectious titers of HAV or HEV by even 2 log cycles at any concentration or time-tested. This study will guide the development of new chemical formulas that will be more effective against major foodborne viruses and will have less impact on food quality and the environment.